Pemodelan Spiritual Leadership, Environmental Justice Orientation, Dan Harmonious Environmental Passion Terhadap OCBE Di Lembaga Keuangan Syariah - Fatmah Bagis; Murtafi'atul Khusna; Erny Rachmawati; Arini Hidayah (Jurnal Ilmiah Ekonomi Islam, 2026)
The transformation towards a sustainable organization requires leaders to be able to instill spiritual and moral values in employees’ behavior. This study aims to analyze the influence of spiritual leadership on Organizational Citizenship Behavior for the Environment (OCBE) with environmental justice orientation as a mediating variable and harmonious environmental passion as a moderating variable in BMT employees. A quantitative approach was used with 190 respondents selected through purposive sampling, and analyzed using SEM-PLS. The results of the study show that spiritual leadership does not have a direct effect on OCBE, but has a positive effect on environmental justice orientation. This orientation was proven to play a significant role in mediating the relationship between the two, while harmonious environmental passion was not proven to be a mediator. These findings emphasize the importance of ecological justice values ​​as a moral mechanism that bridges the influence of spiritual leadership on employee pro-environmental behavior. Theoretically, this study enriches Social Learning Theory, while practically provides recommendations for Islamic financial institutions to strengthen spirituality- and morality-based leadership in promoting a green organizational culture.